Public responses to foreign protectionism: evidence from the US-China trade war - Steinberg, DA; Tan, Y (Springer, 2022)
America’s recent turn towards protectionism has raised concerns over the future viability of the liberal international trading system. This study examines how and why public attitudes towards international trade change when one’s country is targeted by protectionist measures from abroad. To address this question, we fielded three original survey experiments in the country most affected by US protectionism: China. First, we find consistent evidence that US protectionism reduces support for trade among Chinese citizens. We replicate this finding in parallel experiments on technology cooperation, and provide further external validation with a survey experiment in Argentina. Second, we show that responses to US protectionism reflect both a “direct reciprocity” logic, whereby citizens want to retaliate against the US specifically, as well as a “generalized reciprocity” logic that reduces support for trade on a broader, systemic, basis.